Effects of fermentation inoculated lactobacillus on quality and nitrite content of Chinese sauerkraut - YANG Xing-min; LIU Qing-mei; XU Xi-yuan; TANG An-zhang (浙江大学学报. 农业与生命科学版)
The experiment was carried out to test the effects of fermentation by inoculating lactobacillus on quality and nitrite content of Chinese sauerkraut products as compared to natural fermentation. The results showed that not only the rate of production under condition of artificial fermentation was more rapid, but also the products had a lower nitrite content. In addition, no nitrite peak was observed during the whole processing. The key factors that improve the quality of Chinese sauerkraut were the sugar content and lactobacillus inoculated. The optimal condition was found to be a combination of 25 ℃temperature, 4% table salt, 5% sucrose and artificial inoculation of a proper strain of lactobacillus.